2019
DOI: 10.1007/s12028-019-00889-z
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation: Stable Patients Remain Stable 12–24 h Post-tPA

Abstract: Background and Purpose: Stroke patients are currently monitored for neurological deterioration for 24 h following treatment with intravenous tissue plasminogen activator (IV tPA) or mechanical thrombectomy. This requires low nursing ratios and an intensive-care-like setting. As the half-life of IV tPA is short, many patients may not require such prolonged intensive monitoring and could be downgraded much earlier. We evaluate the frequency of neurological deterioration in the 0-12 and 12-24 h post-treatment win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…10 Recent studies have suggested that less frequent assessments, or only 12 hours of intensive care unit monitoring, following alteplase therapy may be reasonable in selected patients. 21,22…”
Section: Alteplase and The Revolution Of Acute Ischemic Stroke Carementioning
confidence: 99%
See 1 more Smart Citation
“…10 Recent studies have suggested that less frequent assessments, or only 12 hours of intensive care unit monitoring, following alteplase therapy may be reasonable in selected patients. 21,22…”
Section: Alteplase and The Revolution Of Acute Ischemic Stroke Carementioning
confidence: 99%
“…10 Recent studies have suggested that less frequent assessments, or only 12 hours of intensive care unit monitoring, following alteplase therapy may be reasonable in selected patients. 21,22 New Frontiers, Challenges, and Future of Thrombolytics in AIS Care Prehospital Alteplase: Mobile Stroke Units and Telestroke Given the early emphasis on time to administration from symptom onset, multiple analyses have highlighted the number needed to treat as low as 4.5 within 1.5 hours compared to 9 within 3 hours and 14 within 3-4.5 hours. 23 The concept of a mobile stroke unit (MSU) for hyperacute stroke treatment was initially proposed in 2003, 23 and proven feasible years later.…”
mentioning
confidence: 99%
“…[5] This feared complication reassuringly occurs in a minority of patients. [6, 7] An earlier retrospective database analysis found a mean time from intravenous tissue plasminogen activator (IV tPA or IV alteplase) administration to END of less than 5 hours, with over 80% of cases occurring within 12 hours. [8] Several factors were predictive of END and any ICH, including an untreated large vessel occlusion and higher baseline NIHSS, consistent with prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…3 Deterioration in patients with no critical care needs after 12 hours in patients with low NIHSS is rare. 4 Because of the COVID-19 pandemic, the need for ICU capacity grew exponentially and the resources available within our ICUs dwindled. Our approach of early transfer out of ICU for post-tPA patients enabled us to optimize available resources within our ICUs.…”
Section: Introductionmentioning
confidence: 99%